Cholestane-3β,5α,6β-triol induces cancer cell death by activating GSDME-mediated pyroptosis - Chen, Jiaxi; He, Yuan; Zhao, Min; Liu, Zihan; Su, Zixin; Li, Chuanzhou; Yang, Chen; Zhang, Jieping; Mao, Shuichun; Han, Hua; Cai, Zhenyu; Zhang, Wen (Frontiers in Pharmacology, 2025)
BackgroundTrihydroxysterols and their analogues accumulate in several pathologies, including neurodegenerative diseases, cancers, and atherosclerosis. Cholestane-3β,5α,6β-triol (CT), recognized as an apoptosis-inducing agent, also exhibits pro-inflammatory effects. Nevertheless, the mechanisms underlying CT-induced cytotoxicity and inflammation remain incompletely characterized.MethodsRNA-sequencing (RNA-seq) analysis indicated CT can stimulate pro-inflammatory cytokine expression. We then employed multiple cell death inhibitors to confirm the predominant form of CT-induced cell death. Using combined chemical inhibition and genetic editing approaches, we established the relationship between caspase 3 activation, CT-mediated gasdermin E (GSDME) cleavage, and subsequent cell death.ResultsCT promotes the expression of multiple pro-inflammatory cytokines. Among inflammatory cell death effector proteins, GSDME was exclusively highly expressed in our cell model. Notably, CT-induced cytotoxicity was abolished by either pharmacological GSDME inhibition or genetic knockdown of GSDME expression. This GSDME-dependent cell death pathway was consistently observed across multiple cell lines. Furthermore, caspase 3 silencing mitigated CT-induced GSDME cleavage, thereby enhancing cell viability.ConclusionCT specifically triggered caspase 3-dependent GSDME cleavage, resulting in pyroptosis as the predominant form of CT-induced cell death. This study establishes a direct mechanistic link between CT and inflammatory cell death execution and provides insight into the contribution of trihydroxysterols to inflammatory pathogenesis.